Mutual benefits? : Investigating a service teaching learning partnership - Graetz, Catherine M. (My University, 2008)
ABSTRACT: The study investigated a service learning partnership between mid-career teachers at a primary school in Atteridgeville and newly-qualified, mostly secondary, teachers from Nottingham University. The aim was to identify benefits and challenges with a view to optimising future partnerships. Data was gathered through participant observation and interviews, analysed by thematic content analysis and interpreted from a critical/postcolonial perspective. The research found a range of benefits accrued to the various stakeholders, including enhanced literacy teaching and learning, opportunities for shared teaching practice, and the lasting legacy of a functional library. While crosscultural contact was identified as a benefit, it also created some tensions related to equitable power-sharing. Therefore, recommendations for future partnerships include clear and consistent communication between partners regarding expectations, goals, and accountability, closer collaboration between partners, and proactive conflict resolution mechanisms. Finally, the research highlights the viable, yet scarcely tapped, potential of such partnerships to address both pre-service and in-service training needs in teacher education in South Africa.
Keywords: service learning; SA education; inset